Minced meat-like products from mealworm larvae (Tenebrio molitor and Alphitobius diaperinus): microbial dynamics during production and storage. (June 2017) - Stoops, J.; Vandeweyer, D.; Crauwels, S.; Verreth, C.; Boeckx, H.; Van Der Borght, M.; Claes, J.; Lievens, B.; Van Campenhout, L.
Abstract: The purpose of this study was to investigate the effect of the production process as well as the storage conditions (air, 60% CO2 /40% N2 ) on the microbial counts and the bacterial community composition of a minced meat-like product from yellow mealworm larvae (YM) and from lesser mealworm larvae (LM). It was necessary to design a different production process for each larva type in order to obtain a minced meat-like product. Both production methods had an effect on the microbiota of the finished products, and that effect was extended during storage. Immediately after production, YM and LM showed aerobic counts between 1.4 and 2.3 log cfu/g and between 2.0 and 3.6 log cfu/g, respectively. The bacterial community composition differed between both products. The use of modified atmosphere during storage reduced bacterial growth compared to storage in air. In conclusion, the study points out that for the two insect types considered, it is possible to obtain a minced meat-like product with low microbial numbers and a potential shelf life that is attractive to retailers and consumers. Industrial relevance: The consumption of traditional meat sources is under pressure due to its high environmental impact. Entomophagy (the consumption of insects by humans) can be one of the solutions to the globally increasing protein demand. However, in Western countries, some aversion for edible insects still exists. In those markets, people prefer the inclusion of insects in an invisible way into familiar food products. In order to stimulate the implementation of edible insects in the Western market, new insect-based products were developed that closely resemble a very popular meat product, being minced meat. Recent studies showed that fresh edible insects contain a high number of spoilage organisms and potential food pathogens. Therefore, monitoring the dynamics of the microbiota during preparation and storage of the new insect-based products is of utmost importance. We were able to produce end products with low microbial numbers that could be kept low during storage, especially by the use of modified atmosphere packaging. Highlights: Two new products were developed, being minced meat from different mealworm larvae. The dynamics of the microbiota during production and storage were monitored. A relation between production processes and survival of microbial counts was found. The effect of the production methods on the microbiota was extended during storage. The insect-based products have a shelf life attractive to retailers and consumers.